TikTok for Assisting Low Motivated EFL Students in English Conversation (A Case Study at One of Private Vocational Schools in Ciamis) - Herdiana, Hasya Ajriya; Rohayati, Dedeh; Faridah, Didih (Universitas Galuh, 2025)
The study highlights the need to accommodate individual preferences and comfort levels in using the TikTok applications for language learning. This study aims to investigate the difficulties students face in performing English conversations and to analyze the students’ perceptions of using the TikTok application to perform English conversations. The present study employed qualitative paradigm using the type of case study and was conducted at one of the vocational schools in Ciamis. Additionally, the researcher used interviews and observation to answer the research objectives. The study discovered that students faced several challenges in creating content. Technical issues, such as video errors and slow upload times, were common obstacles. Additionally, environmental factors, such as background noise, often interfere with the quality of their videos. On a personal level, difficulties with language proficiency and a lack of confidence in content creation further complicated the process. These challenges underscore the importance of providing support and guidance for integrating TikTok as an educational tool effectively. However, the findings showed that TikTok has an appeal as an English language learning medium, particularly in developing speaking skills and boosting student confidence. A highly positive student responds to learning to speak through the TikTok Application because it fosters enthusiasm, motivation, and comfort in English conversation performance.